Perempuan Adalah Pencari Nafkah Dan Laki-laki Adalah Ibu Rumah Tangga: Sosialisasi Gender Dalam Budaya, Masyarakat, Dan Pendidikan - Gani, Rusna (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2022)
The purpose of this paper is to examine the impact of gender socialization on culture, society, and education, with a focus on how the cultural and social conditioning of students and teachers influences their behavior in educational settings. To answer the question of what gender norms and beliefs a teacher transmits to the classroom, this paper examines how society and culture reinforce gender roles in education. Examples of gender socialization, gender roles, and gender stereotypes are used to distinguish inequalities in teaching students of different sexes and genders. This paper further analyzes how teacher biases can undermine their students' learning and how social norms are maintained through self-fulfilling prophecies. Finally, the importance of gender competence for teachers is highlighted and the importance of gender equality, as a powerful way to ensure that students are given fair opportunities in education, is brought to the fore.